Alcohol Intake Investigation of Adult Rats Based on Sperm Parameters - Anam, Choirul; Warih Marhendra, Agung Pramana; Rahayu, Sri (Graduate School, Universitas Brawijaya, 2019)
The prevalence of alcohol consumption is high among adult males during the reproductive period. The current study aimed to evaluate the impact of chronic administration ethanol on the quality of sperm in the rats. Twelve healthy Wistar male albino rats were randomly divided into 2 groups to represent the 2 phase duration. The first phase lasted 21 days and the second phase lasted 49 days. In each phase, the animals were separated into subgroups: A and B. Subgroup A represented control that received distilled water while subgroup B represented animals that received 7 mL.kgBW-1 of 30% ethanol per day, thrice a week. The data were analyzed using ANOVA (P<0.05). There is no significant difference in sperm concentration and viability. However, there is a significant difference in the motility of spermatozoa between the control group and ethanol-treated group. Thus, the study indicates that ethanol administration may disturb the sperm motility and have no clear effect on its concentration and viability.Keywords: alcohol consumption, reproductive function, sperm quality.